The Role of Managerial Social Capital Head of Police Sector in Strengthening the Influence of Human Capital Leaders on Human Relations - Adisatria, Wiwit; Sabar; Juansih (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Purpose - Leader human capital in the police sector refers to a leader with the knowledge, skills, and experience to develop and use human resources. Police leaders face a daunting task in developing human capital and turning it into organizational learning. This study examines the interplay between human capital and social capital, how it impacts human relationships, and the effectiveness of public security and order. Design/methodology/approach - This study uses a quantitative approach, using a survey method, with the unit of analysis being the Police Sector and using multisource data sources, with a total sample of 82 respondents. Data collection for this study used a questionnaire with self-reported data. Findings – This research found that the police chief's social capital management strengthens his human capital's influence on human connections. This suggests that the police chief's human capital and capacity can develop relationships. The test results also reveal that human relations affect police security and social services. The test results demonstrate that human capital does not improve police security and social services. Testing this model shows that human capital affects public security and order more effectively through human relations. Originality/Value - This study investigates the interplay between social and human capital, focusing on their impact on security effectiveness and human relations within the Police as a command organization. Policy Implication - Investing in human resource development and promoting strong human connections within the police sector is crucial to enhance the efficacy of security and social services.